Pathogenicity and immunosuppressive properties of GM-97 strain of infectious bursal disease virus in commercial broiler chickens - Murmu, Rozina; Islam, Md Nazrul; Juli, Most. Sogra Banu; Khan, Md Abu Sayed; Harun-ur-Rashid, SM; Hossain, Ferdaus Moyd. Altaf; Rahman, Md Masudur (Journal of Advanced Veterinary and Animal Research, 2014)
The current study was conducted to evaluate the pathogenicity and immunosuppressive effects of GM-97 strain of infectious bursal disease virus in commercial broiler chickens. A total of 500 broiler chickens were vaccinated with the virus through oral route at 10 and 17 days of age (102-103 EID50/dose). Chickens were also vaccinated with Newcastle disease virus (Hitchner B1) orally at 14 and 21 days old. Chickens were euthanized (at 12, 14, 16, 20, 23, 26 days of age) after measuring body weight. Bursa of Fabricius was examined for any gross lesion, weighed and processed for histological investigations. Bursa to body weight ratio and bursal lesion scoring were made to evaluate pathogenicity of the virus. Blood samples were analyzed for antibody response to ND vaccine virus using HI test. Results showed that the GM-97 strain of IBDV induced mild to moderate depletion of lymphoid cells in the center of bursal follicles and non-significant difference in bursa to body weight ratio amongst vaccinated and unvacci-nated chickens. Chickens responded well to ND vaccine by mounting high level of serum NDV specific HI antibody titers. It can be concluded from the present study that GM-97 strain of IBDV has mild pathogenicity but is not immunosuppressive. DOI: http://dx.doi.org/10.5455/javar.v1i1p1-7 J. Adv. Vet. Anim. Res., 1(1): 1-7, March 2014